Pelayanan Kesehatan pada Lansia di Panti Sosial Tresna Werdha Madago Tentena - Agusrianto, Agusrianto; Langitan, Rosamey Elleke; Manggasa, Dafrosia Darmi Manggasa; Suharto, Dewi Nurviana; Ndama, Metrys; Rantesigi, Nirva; Parwata, Ni Made Ridla Nilasanti; Hermanto, Raden Bagus Bambang (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Elderly individuals generally undergo various physical and health changes. They tend to be more susceptible to various chronic diseases, such as diabetes, hypertension, arthritis, and neurological disorders like dementia. Therefore, they require specialized care and ongoing monitoring. These efforts can help prevent diseases and enhance the quality of life for the elderly. Some of the main issues frequently faced by elderly individuals living in nursing homes are related to their health, including chronic diseases, mental disorders, and physical decline. The goal of this community service is to make a tangible contribution to improving elderly healthcare services through collaboration between the community service team and the staff of the independent living facility.The target of this community service team is 63 elderly individuals residing at PTSW Madago Tentena. The results of the community service activities indicate that most of the elderly residents at PTSW suffer from chronic diseases, including 13 individuals (20.64%) with diabetes mellitus, 41 (65.1%) with hypertension, 2 (3.2%) with severe cognitive impairment, and 5 (7.9%) with mild cognitive impairment. The health status is categorized as severe for 8 (12%), moderate for 30 (48%), and mild for 25 (40%). Therefore, the outcomes of this community service can serve as a reference for the nursing home staff to strive for improved health among the elderly and collaborate with other institutions to provide healthcare services in the facility.